2004
DOI: 10.1007/s00213-003-1676-7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of functional activity associated with cocaine self-administration in the rat change over time

Abstract: These data demonstrate that the distribution of functional activity associated with self-administered cocaine undergoes considerable change over the course of drug exposure. While increases in metabolic rates were largely found in autonomic and sensorimotor structures after short-term cocaine access, decreases were prominent in mesocorticolimbic regions after prolonged exposure. These differences in the patterns of brain activity that develop with long-term cocaine self-administration may play a role in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 46 publications
(67 reference statements)
2
9
0
Order By: Relevance
“…Furthermore, 74 of the 90 genes (including the 32 genes that were significantly downregulated) displayed reduced expression levels in cocaine addicts. These findings were also highly consistent with previous brain imaging studies that have revealed negative effects of cocaine on brain glucose metabolism (London et al, 1990; Lyons, Friedman, Nader, & Porrino, 1996; Macey, Rice, Freedland, Whitlow, & Porrino, 2004; Thanos, Michaelides, Benveniste, Wang, & Volkow, 2008). Furthermore, alteration of certain genes encoding for mitochondrial components induced by cocaine (Lehrmann et al, 2003) and nicotine (Wang, Kim, Donovan, Becker, & Li, 2009) exposure had also been reported previously.…”
Section: Molecular Adaptations Accompanying Early Response and Lonsupporting
confidence: 91%
“…Furthermore, 74 of the 90 genes (including the 32 genes that were significantly downregulated) displayed reduced expression levels in cocaine addicts. These findings were also highly consistent with previous brain imaging studies that have revealed negative effects of cocaine on brain glucose metabolism (London et al, 1990; Lyons, Friedman, Nader, & Porrino, 1996; Macey, Rice, Freedland, Whitlow, & Porrino, 2004; Thanos, Michaelides, Benveniste, Wang, & Volkow, 2008). Furthermore, alteration of certain genes encoding for mitochondrial components induced by cocaine (Lehrmann et al, 2003) and nicotine (Wang, Kim, Donovan, Becker, & Li, 2009) exposure had also been reported previously.…”
Section: Molecular Adaptations Accompanying Early Response and Lonsupporting
confidence: 91%
“…Macey and colleagues [64] observed decreased glucose metabolism in the dorsolateral striatum after 60 hours of cocaine self-administration (2 hour daily sessions over 30 days). Similarly, a decrease was observed in dorsolateral striatum single neuron firing rates during instrumental movements over 28 hours of water self-administration (2 hour daily sessions over 14 days; [65]).…”
Section: Discussionmentioning
confidence: 99%
“…In the water-seeking experiment, animals acquired a habit, as evidenced by maintained operant movements despite prior satiation with water. In the cocaine-seeking experiment [64], although habit formation was not tested, neural activity of dorsolateral striatum neurons could be interpreted as a correlate of habit formation.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence indicates that cortical activity decreases during cocaine withdrawal (e.g. humans: Volkow et al, 1992; Goldstein and Volkow, 2002; primates: Beveridge et al, 2006; Porrino et al, 2007; rats: Hammer et al, 1993; Macey et al, 2004; Sun & Rebec, 2006). A resultant decrease in the activity of glutamate projections to the NAc could lead to a synaptic scaling-mediated increase in AMPAR levels on MSN (see Sun and Wolf, 2009 for discussion).…”
Section: Ampar Transmission In the Nac During Incubationmentioning
confidence: 99%